PRANGOS ABIETICOLA (APIACEAE), A NEW SPECIES FROM SOUTH ANATOLIA, TURKEY - Aytaç, Z.; Duman, H. (Edinburgh Journal of Botany, 2016)
Prangos abieticola Aytaç & H.Duman (Apiaceae) from southern Anatolia, Turkey is described and illustrated. This new taxon grows on calcareous rocks in open Abies cilicica (Antoine & Kotschy) Carrière and Pinus nigra J.F.Arnold subsp. nigra var. caramanica (Loudon) Rehder forest in the middle of the Taurus Mountains (C3 Antalya and Konya Province). It is endemic and closely related to Prangos heyniae H.Duman & M.F.Watson and P. ferulacea (L.) Lindl. The diagnostic morphological characters of similar taxa are discussed.
Keywords: Anatolia; Apiaceae; new species; Prangos; Turkey